2010
DOI: 10.1002/asi.21327
|View full text |Cite
|
Sign up to set email alerts
|

Search behavior of media professionals at an audiovisual archive: A transaction log analysis

Abstract: Finding audiovisual material for reuse in new programs is an important activity for news producers, documentary makers, and other media professionals. Such professionals are typically served by an audiovisual broadcast archive. We report on a study of the transaction logs of one such archive. The analysis includes an investigation of commercial orders made by the media professionals and a characterization of sessions, queries, and the content of terms recorded in the logs. One of our key findings is that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 24 publications
(43 reference statements)
3
101
1
Order By: Relevance
“…System-centered research about media professionals' use of archival material concludes that these users have a strong demand for short excerpts of audiovisual material, and that search queries are often based on the titles of materials or names of specific people (Huurnink et al, 2010). Search behavior is furthermore divided into specific search modi such as browsing, topic selecting, querying and locating (Kouwenhoven, 2006), all of which occur within the industrial constraint of short deadlines.…”
Section: Serendipitous Search Behaviour and Creative Retrievalmentioning
confidence: 99%
See 2 more Smart Citations
“…System-centered research about media professionals' use of archival material concludes that these users have a strong demand for short excerpts of audiovisual material, and that search queries are often based on the titles of materials or names of specific people (Huurnink et al, 2010). Search behavior is furthermore divided into specific search modi such as browsing, topic selecting, querying and locating (Kouwenhoven, 2006), all of which occur within the industrial constraint of short deadlines.…”
Section: Serendipitous Search Behaviour and Creative Retrievalmentioning
confidence: 99%
“…Media professionals -such as news editors, image researchers, and documentary filmmakersincreasingly rely on online access to digital content within audiovisual archives to create narratives (Huurnink, Hollink, & De Rijke, 2010). Searching and retrieving audiovisual sources within archives therefore requires an in-depth knowledge of how to find sources digitally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They conclude, that "[s]earching the spoken word imposes demands on both system and searcher that differ from those involved in searching the written word" [2, p. 338]. Recently, Huurnink et al [7] studied media professionals' use of an audiovisual archive through transaction log analysis. The results of the study show that (i) over half of the sessions were completed in less than 1 minute; (ii) nearly all of the queries contained a free text keyword search while almost a fourth specified a date filter.…”
Section: User Needs In Sound Retrievalmentioning
confidence: 99%
“…Program title was the most frequently occurring keyword search; (iii) the advanced search options was used in only 9% of the queries with media format and copyright owner as the most frequently specified metadata; (iv) finally, three different units of ordering was identified (programs, stories, and fragments) pointing to a need to address several indexing levels. The study by [7] took place within the context of a large broadcast archive containing both video and audio resources. They did not distinguish between the two media types, but the study revealed that less than 10% of the clicks and orders to the archive were for audio material.…”
Section: User Needs In Sound Retrievalmentioning
confidence: 99%